Field application of silicon alleviates drought stress and improves water use efficiency in wheat - Johnson, Scott N.; Chen, Zhong-Hua; Rowe, Rhiannon C.; Tissue, David T. (Frontiers in Plant Science, 2022)
Detrimental impacts of drought on crop yield have tripled in the last 50 years with climate models predicting that the frequency of such droughts will intensify in the future. Silicon (Si) accumulation, especially in Poaceae crops such as wheat (Triticum aestivum L.), may alleviate the adverse impacts of drought. We have very limited information, however, about whether Si supplementation could alleviate the impacts of drought under field conditions and no studies have specifically manipulated rainfall. Using field–based rain exclusion shelters, we determined whether Si supplementation (equivalent to 39, 78 and 117 kg ha-1) affected T. aestivum growth, elemental chemistry [Si, carbon (C) and nitrogen (N)], physiology (rates of photosynthesis, transpiration, stomatal conductance, and water use efficiency) and yield (grain production) under ambient and drought (–50% of ambient) rainfall scenarios. Averaged across Si treatments, drought reduced shoot mass by 21% and grain production by 18%. Si supplementation increased shoot mass by up to 43% and 73% in ambient and drought water treatments, respectively, and restored grain production in droughted plants to levels comparable with plants supplied with ambient rainfall. Si supplementation increased leaf-level water use efficiency by 32–74%, depending on Si supplementation rates. Water supply and Si supplementation did not alter concentrations of C and N, but Si supplementation increased shoot C content by 39% and 83% under ambient and drought conditions, respectively. This equates to an increase from 6.4 to 8.9 tonnes C ha-1 and from 4.03 to 7.35 tonnes C ha-1 under ambient and drought conditions, respectively. We conclude that Si supplementation ameliorated the negative impacts of drought on T. aestivum growth and grain yield, potentially through its beneficial impacts on water use efficiency. Moreover, the beneficial impacts of Si on plant growth and C storage may render Si supplementation a useful tool for both drought mitigation and C sequestration.